Excitonic bandgap dependence on stacking configuration in four layer graphene - Goolaup, Sarjoosing (2014)
Different crystallographic stacking configurations in graphene provide an additional degree of freedom in the electronic structure. We have conducted systematic investigations of the transport properties of ABAB- and ABCA-stacked four-layer graphene. Our results reveal that ABAB and ABCA graphene exhibit markedly different properties as functions of both temperature and magnetic field. The temperature-dependant resistance measurement reveals that the excitonic gap of ABCA stacked graphene increases as a function of temperature, while for ABAB, a shrinking excitonic gap configuration is observed.